Health statistics in international databases and their cartographic visualization - Štampach, Radim; Geryk, Edvard (Quaestiones Geographicae, 2012)
For health system management, relevant data and information are necessary. The first part of the paper describes databases of the important health data providers WHO, OECD, IARC and Eurostat. It analyses whether they are in discrepancy and whether it is possible to combine data from different databases. Cartographic visualization can be used for the analysis of situations and also for the publishing of statistics and other information. Selected international providers offering health maps are evaluated in the second part of the paper. There are differences in the possibilities offered to the user and in the quality of the provided maps.